Query 115

#$&*

course Mth 277

11/19 8

11.5*********************************************

Question: `q001.

Let z = f(x,y) = xy + 1 where x = cos 3t and y = cot 3t.

Find dz/dt after finding z explicitly in terms of t.

Use the chain rule for one parameter to find dz/dt.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

dz/dt = -3cot(3t)(sin(3t)) + (-3cos(3t)(csc^2*3t) )

just did chain rule

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

z = x y + 1 = cos(3t) * cot(3 t) + 1, so

dz/dt = (cos(3t)) ' cot(3t) + cos(3t) (cot(3t) ) ' = -3 sin(3t) cot(3t) - cos(3 t) sec^2(3 t), which could be simplified.

Using the chain rule

dz/dt = dz/dx dx/dt + dz/dy dy/dt

= y * (-3 sin(3t) ) + x * (-sec^2(3 t))

= -3 sin(3 t) cot(3 t) + cos(3 t) * (-sec^2(3 t) ),

which could also be simplified but is clearly equal to the previous expression.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

in your dz/dt I think you left 3 off of - cos(3t) sec^2(3t) because u = 3t and u' = 3

------------------------------------------------

Self-critique rating:

@&

That's right. Good.

*@

*********************************************

Question: `q002.

Let F(x,y) = x^2 + y^2 where x(u,v) = u cos(v) and y(u,v) = u + v^2. Let z = F(x(u,v),y(u,v)). Find z_u and z_v in the following ways.

Expressing z explicitly in terms of u and v.

Apply the chain rule for two independent parameters.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

to get total change in F, get smaller change in (x,y) and even smaller change in x(u,v) and y(u,v). so start smallest.

start with knowing the equation dF/dz = dz/du + dz/dv

so solve for dz/du and dz/dv, (i think i'm going the right direction)

F_x = 2x and F_y = 2y

z_u = 2ucos^2(v) + 2u +2v^2+v^4

z_v = -2u^2sin(v)cos(v) + u^2 + 4uv + 4v^3

with that get your equations you need to solve for dz/du = dz/dx * dx/du + dz/dy * dy/du and also the equation dz/dv = dz/dx * dz/dv + dz/dy * dy/dv

you get these from what we were given x(u,v) = ucos(v) and y(u,v) = u + v^2

dx/du = cos(v)

dx/dv = -usin(v)

dy/du = 1

dy/dv = 2v

put into equations and get that dz/du = 2x(cos(v)) + 2y and dz/dv = 2x(-usin(v)) + 4yv

of corse you can simplify this, but the total dF/dz is those two added together.

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

z = x^2 + y^2 = (u cos(v))^2 + (u + v^2) ^ 2 = u^2 cos^2(v) + u^2 + 2 u v^2 + v^4.

So

z_u = 2 u cos^2(v) + 2 u + 2 v^2

and

z_v = -2 u^2 cos(v) sin(v) + 4 u v + 4 v^3.

Applying the chain rule:

F_x = 2 x and F_y = 2 y.

dx/du = cos(v), dx/dv = - u sin(v), dy/du = 1 and dy/dv = 2 v. Thus

dz/du = dz/dx * dx/du + dz/dy * dy/du

= 2 x * cos(v) * 2 v + 2 y * 1

= 2 u cos(v) * cos(v) + 2 (u + v^2) * 1.

When simplified this agrees with our previous result z_u = 2 u cos^2(v) + 2 u + 2 v^2 .

dz/dv works out in an analogous manner.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

z_u should have +v^4 on the end

z_v should have +u^2 in the middle of that

???????? in your equation for dz/du you have = dz/dx*dx/du at the start.

well dz/du i can see is just F_x_u which is 2x. so you fill in 2x*(cos(v)). and thats it. why do you have * 2v in there with it????

there are similarities in our answers but this is a pretty tedious situation

@&

Just to be sure:

A change in u results in a change in x, at the rate dx/du.

A change in x in turn results in a change in F, at the rate dF/dx.

So, through its effect on the value of x, a change in u will change the value of F at the rate dF/dx * dx/du, o

which can also be expressed as F_x * x_u.

*@

------------------------------------------------

Self-critique rating:

*********************************************

Question: `q003. Find w_r where w = e^(x - y + 3z^2) and x = r + t - s, y = 3r - 2t, z = sin(rst).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I have gotten 18sin(x)cos(x)*e^( (r+s+t) -3r + 2t +3sin^2(rst) )

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

w_r can be written dw/dr, and we have

dw/dr = dw/dx dx/dr + dw/dy dy/dr + dw/dz dz/dr

= e^(x - y + 3 z^2) * 1 - e^(x - y + 3 z^2) * 3 + 6 z e^(x - y + 3 z^2) * (r s) cos(r s t).

Simplifying and substituting for x, y and z we get

(-2 + 6 sin(rst) ) e^(-2 r + 3 t + 3 ( sin^2(rst)) )

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok here i only took the partial derivative of r in the function w. did not include dw/dx and all that jazz.

I failed to realize that there is indivual x,y,and z terms here, because i substituted early in for x,y, and z into the origional equation ""masking"" the x,y, and z terms

but i see how you got this, it is similar to the past problems and I'm sure i could do this if i worked carefully enough.

------------------------------------------------

Self-critique rating:

*********************************************

Question: `q004. The combined resistance of three resistors R is given by the formula 1/R = 1/(R1) + 1/(R2) + 1/(R3). Suppose that at a certain instant R1 = 150 ohm, R2 = 300 ohm,

and R3 = 450 ohm. R1 and R3 are decreasing at a rate of 3 ohm/sec and R2 is increasing at a rate of 4 ohm/sec. How fast is R changing at this instant and is it increasing or decreasing?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

decreasing by 0.0000025 ohm/s

(1/900) - (1/898) = that ^^

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Regarding R, R1, R2 and R3 as functions of t, we take the t derivative of both sides and get

-1/R^2 dR/dt = -1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt

so that

dR/dt = (-1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt) * R^2

Substituting the given values for the three resistances and the three rates of change we get

dR/dt = (-1 / (150 ohms)^2 * (-3 ohms/sec) - 1 / (300 ohms) * (+4 ohms/sec) - 1 / (450 ohms) * (-3 ohms/sec) ) * R^2

= 7 / (67500 ohm sec) * (900/11 ohms) ^2

= .69 ohms / sec, approx..

You can verify that for the given values of R1, R2 and R3 we get R = 900/11.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok didn't realize that because it was a function of t that you had to take deriv. but I understand it

******************** end of frs to here

snd follows ************

start

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question: `q004. The combined resistance of three resistors R is given by the formula 1/R = 1/(R1) + 1/(R2) + 1/(R3). Suppose that at a certain instant R1 = 150 ohm, R2 = 300 ohm,

and R3 = 450 ohm. R1 and R3 are decreasing at a rate of 3 ohm/sec and R2 is increasing at a rate of 4 ohm/sec. How fast is R changing at this instant and is it increasing or decreasing?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

decreasing by 0.0000025 ohm/s

(1/900) - (1/898) = that ^^

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Regarding R, R1, R2 and R3 as functions of t, we take the t derivative of both sides and get

-1/R^2 dR/dt = -1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt

so that

dR/dt = (-1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt) * R^2

Substituting the given values for the three resistances and the three rates of change we get

dR/dt = (-1 / (150 ohms)^2 * (-3 ohms/sec) - 1 / (300 ohms) * (+4 ohms/sec) - 1 / (450 ohms) * (-3 ohms/sec) ) * R^2

= 7 / (67500 ohm sec) * (900/11 ohms) ^2

= .69 ohms / sec, approx..

You can verify that for the given values of R1, R2 and R3 we get R = 900/11.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok didn't realize that because it was a function of t that you had to take deriv. but I understand it

******************** end of frs to here

snd follows ************

start

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

*********************************************

Question: `q004. The combined resistance of three resistors R is given by the formula 1/R = 1/(R1) + 1/(R2) + 1/(R3). Suppose that at a certain instant R1 = 150 ohm, R2 = 300 ohm,

and R3 = 450 ohm. R1 and R3 are decreasing at a rate of 3 ohm/sec and R2 is increasing at a rate of 4 ohm/sec. How fast is R changing at this instant and is it increasing or decreasing?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

decreasing by 0.0000025 ohm/s

(1/900) - (1/898) = that ^^

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Regarding R, R1, R2 and R3 as functions of t, we take the t derivative of both sides and get

-1/R^2 dR/dt = -1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt

so that

dR/dt = (-1/R1^2 d(R1)/dt -1/R2^2 d(R2)/dt -1/R3^2 d(R3)/dt) * R^2

Substituting the given values for the three resistances and the three rates of change we get

dR/dt = (-1 / (150 ohms)^2 * (-3 ohms/sec) - 1 / (300 ohms) * (+4 ohms/sec) - 1 / (450 ohms) * (-3 ohms/sec) ) * R^2

= 7 / (67500 ohm sec) * (900/11 ohms) ^2

= .69 ohms / sec, approx..

You can verify that for the given values of R1, R2 and R3 we get R = 900/11.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok didn't realize that because it was a function of t that you had to take deriv. but I understand it

******************** end of frs to here

snd follows ************

start

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!#*&!

@&

Be sure to check my notes and let me know if you don't understand.

*@